The Effect of Health Education: Husband’s Support for Postpartum at Bhayangkara Hospital Kupang - Yosina Martha Tamonob; Mira Triharini; Retnayu Pradanie (Universitas Airlangga, 2016)
Introduction: One of Social support for postpartum was comes from husband. Support is an assist form which is felt bysomeone that comes from interpersonal relationship. Support from husband is an important factor that contributeto decrease fatigue and improve maternal health of a postpartum mother. An effort toincrease husband’s support for the mother is by giving health education. Methods: Design used inthis research was quasy - experiment with post test only control group design. The population was postpartum mothers atBhayangkara Hospital Kupang. Twenty couple matched the inclusion and exclusion criteria became the sample.Independent variable was health education and the dependent variable was husband’s support. Data wereanalyzed using Mann Whitney test with level of significance α=0.05. Results: The results showed that healtheducation increase husband's support for postpartum mothers with p=0.00. Discussion: The study, concluded that healtheducation improve husband’s support for postpartum mother at Bhayangkara Hospital Kupang. This can be thefirst step for midwives and nurses to provide further health education related to the husband 's support for postpartum.